Communication Failure, Esteem Level, and Responsibility A Willingness to Try Again - Derr, William R. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
Noting that communication apprehension contributes to failed communication, which in turn places business organizations at risk, this paper describes the rationale and methodology of a study to determine whether managers can predict an employee's sense of responsibility and willingness to improve following an incident of failure, based on the employee's level of communication apprehension or level of self-esteem. The first half of the paper discusses the interrelationship of communication apprehension and failure, hypothesizing that if managers know an employee's level of communication apprehension, self-esteem may be predicted, thereby enabling them to predict the employee's resilience after failure and reducing the organizational risk. The second half of the paper describes the methodology and results of a study to determine whether the Personal Report of Communication Apprehension and the Janis-Field Self-Esteem Scale are inversely correlated and can be used by managers as cross-predictive tools. The paper concludes that (1) the significant inverse correlation between the two instruments indicates that they can be used to cross-predict either self-esteem level or communication apprehension, and (2) high self-esteem/low communication apprehension employees appear to be higher risk-takers who characterize their failures as positive, who take responsibility for their actions, and who to intensify their efforts to succeed after failure, thereby placing their organizations at a lower degree of risk than those with low self-esteem and high communication apprehension. (HTH)
ERIC Note: Paper presented at the Annual Meeting of the Western Speech Communication Association (Fresno, CA, February 16-19, 1985).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Apprehension; Communication Research; Employee Attitudes; Employer Employee Relationship; Failure; Interpersonal Communication; Organizational Communication; Organizational Effectiveness; Self Esteem; Reports, Research; Speeches/Meeting Papers